Paradigm Shift of Microfinance Institutions in Nepal: A Mixed Method Approach - Sherpa, Sanjib (NRB Economic Review, 2025)
This study examines how the transformation of MFIs from non-profit to profit-oriented has impacted their performance in Nepal. A mixed-method approach was applied where quantitative data was analysed using a Propensity Score Matching (PSM), followed by a qualitative thematic analysis. The results show that the transformation of MFIs reduces their profitability and operational self-sufficiency in the short run but increases them in the long run. Furthermore, the study found that the number of clients and the loan size of profit-oriented MFIs are increasing in Nepal, which suggests that MFIs in Nepal are drifting away from their main mission of social welfare, also known as mission drift.